STRUKTUR, MAKNA, DAN FUNGSI MANTRA PENGOBATAN MASYARAKAT MELAYU KABUPATEN BENGKAYANG - Sentosa, Adi; Sulissusiawan, Ahadi; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractMantra is one of the old types of Malay poetry believed to contain supernatural powers and supernatural powers. The reason the researcher chose the title of the research Structure, Meaning, and Function of the Medical Spell of Bengkayang Regency Malay Community based on several considerations. Common problems in this study are the structure (rhyme and diction), the meaning, and function of the treatment mantra.Â Theories used in this research are oral literary theory, mantra, mantra structure, mantra meaning, mantra function, translation theory. This research method is descriptive, the form of this research is qualitative research, this research approach is a semiotic structural approach. Based on the results of data analysis of the Malay community medical treatment spells in Bentarat Hamlet Bengkayang Regency, there are rhymes according to the words in the words include: full rhyme, absolute rhyme, half rhyme, rhyme alliteration, and rhyme asonance, Rima according to its location in sentence lines which include: initial rhymes, and final rhymes. Dictations in medical spells are denotative words and connotative words. The meaning of mantra medicine is religious meaning. The function of the treatment mantra is the function of the mantra as a projection system.Â Keywords: Function, Meaning, Structure, and Treatment Mantra